Relação entre comportamento governado por regras e indicadores de depressão em estudantes universitárias - Basaglia, Marina Aoki (2022)
A verbal instruction that describes a contingency is considered, for Behavior Analysis, as a rule, which can exert control over a person's behavior. A rule can be followed for different reasons, that is, different variables can control rule-governed behavior. When someone behaves according to what is described by the rule, depending on the described consequence, it is tracking. On the other hand, when someone behaves in accordance with the rule due to the issuer of the rule (that is, under control of social consequences), it is pliance. Behavior learned from following rules has the advantage of being acquired more quickly than being solely under the control of contingencies. However, it is not always possible to get reinforcement by following a rule. The imbalance between rule-following behavior can generate a series of avertive events, which may be related to depression. Considering that the data presented in the literature on the relationship between rule-following behavior and depression are still inconsistent, the aim of this study is to verify whether the severity of depression symptoms can influence the likelihood of rule-following behavior even if they become inconsistent, as well as possible variables that may interact with symptoms and affect the probability of following rules, even if discrepant. 17 female university students participated in this study. To verify the possibility of depressive symptoms, the PROMIS II Depression was used. 8 participants had high indicators of depressive symptoms, and 9 participants had low indicators. Participants were further divided into tracking, pliance with monitoring and pliance without monitoring groups. The experiment consisted of a task that used the PsychoPy software, and took place remotely. When starting the task, each participant was instructed to choose, among two figures that appeared on the screen, a figure equal to the model if a green circle appeared, or a different figure if a red circle appeared. Each correct answer was signaled with an addition of points on the scoreboard that appeared on the screen and with the sound of clapping. Incorrect answers were signaled with the sound of a horn and withdrawal of points. The task was divided into Pre-Training, Phase 1 of Training and Phase 2 of Training, the latter being divided into 4 blocks of 20 attempts each, without signaling that there was a block change. The second and fourth blocks had contrary contingencies in relation to the instruction provided at the beginning of the experiment. The results pointed to a tendency for participants with high indicators of depression symptoms to change their response when the rule stopped working. It was also observed that in the pliance condition these participants changed their response more quickly compared to the tracking condition, which may indicate a possible control exercised by the social agent.